2020
DOI: 10.1111/ijcp.13499
|View full text |Cite
|
Sign up to set email alerts
|

The current debate over treatment of subclinical hypothyroidism to prevent cardiovascular complications

Abstract: Background Subclinical hypothyroidism (SCH) is an asymptomatic condition associated with increased thyroid‐stimulating hormone (TSH) >4 mIU/L with normal thyroxine (T4) and triidothyronine (T3) levels. It is more common in older subjects and especially in women with an overall incidence of 10%. Objective Because the normal TSH levels increase with age up to 7.5 mIU/L in older people, several studies have reported either no benefits whereas others have reported the benefits of treatment. These studies have caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 68 publications
(161 reference statements)
0
9
0
1
Order By: Relevance
“…Increased blood pressure in SCH may be a result of reduced thyroid hormone-mediated endothelialdependent vasodilation (16). Specific to dyslipidemia, decreased activity of both lipoprotein lipase activity in adipose tissue and hepatic lipase activity in the liver are thought to contribute to increased serum triglyceride levels (17). A reduced number of lowdensity lipoprotein (LDL) receptors and decreased cholesterol breakdown may also explain the dyslipidemia seen in SCH (16).…”
Section: Pathophysiology Of Cardiovascular Disease (Cvd) Related To Schmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased blood pressure in SCH may be a result of reduced thyroid hormone-mediated endothelialdependent vasodilation (16). Specific to dyslipidemia, decreased activity of both lipoprotein lipase activity in adipose tissue and hepatic lipase activity in the liver are thought to contribute to increased serum triglyceride levels (17). A reduced number of lowdensity lipoprotein (LDL) receptors and decreased cholesterol breakdown may also explain the dyslipidemia seen in SCH (16).…”
Section: Pathophysiology Of Cardiovascular Disease (Cvd) Related To Schmentioning
confidence: 99%
“…In addition to increasing metabolic risk factors, SCH may negatively impact cardiac function itself, with studies demonstrating a possible role of liothyronine (T3) in mitochondrial function and repair/ damage (18) and the improvement of cardiac output and reduction of peripheral vascular resistance upon T3 administration (19). Other studies have found that SCH is also associated with decreased ejection fraction, decreased arterial compliance, and increased risk of heart failure, possibly through increased reninangiotensin-aldosterone axis activation, increased vasoconstriction, increased sympathetic activity, and reduced renal blood flow and glomerular filtration rates (16,17).…”
Section: Pathophysiology Of Cardiovascular Disease (Cvd) Related To Schmentioning
confidence: 99%
“…Other studies have shown that subclinical hypothyroidism can increase creatinine levels and ultimately decrease GFR [23,24]. Another hypothesis about the association between subclinical hypothyroidism and albuminuria is decreased cardiac output and increased peripheral vascular resistance in these patients [25,26]. Recent studies have shown that patients with subclinical hypothyroidism develop disorders in vascular endothelial structure through reduced endothelium-related vasodilation and nitric oxide disorders, leading to an increase in albuminuria and impaired renal function in these patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Graves' hyperthyroidism is frequently manifested by systemic symptoms such as dermopathy, ophthalmopathy, and acropathy with high affinity to recurrence even after different therapeutic options [4]. More importantly, the likelihood of cardiovascular morbidity and mortality can also rise due to hyperthyroidism flare [5,6].…”
Section: Introductionmentioning
confidence: 99%